Circuit analysis of radiation reaction in metamaterials by retarded electromagnetic coupling - Ryoma Nakata; Takashi Hisakado; Tohlu Matsushima; Osami Wada (IET Circuits, Devices and Systems)
Abstract Because radiation is essential in high‐frequency circuits, such as those used in metamaterials and plasmonics, the investigation of radiation loss is important. This study describes the characteristics of radiation loss, which is a radiation reaction in circuits with retarded electromagnetic couplings. The structure of wired metallic spheres is used to demonstrate metamaterial equivalent circuits, where charges and current exist on the spheres and wires, respectively. An inductance matrix and a potential coefficient matrix with retarded electromagnetic couplings are defined to address the radiation reaction. Subsequently, based on the topology of the wires and spheres, an equivalent circuit equation with retardation is formulated to discuss the losses in the resonant circuit caused by the inductive and capacitive elements. Thereafter, the relationship between the resonant frequency and radiation loss caused by the retarded couplings is demonstrated and the difference between the retarded couplings and couplings with transmission lines is clarified. Furthermore, we indicate that retarded coupling generates singularity on a dispersion curve for a one‐dimensional array of resonant circuits. Thus, the circuit with retarded couplings generates novel characteristics of radiation reactions that are not represented by the circuit without retardation. This circuit analysis is expected to afford new aspects in studies on topics, such as metamaterials and plasmonics.